The cities that never were (?). Connectivity between urban settlements and the rural landscape in Lusitania during Late Antiquity - Carneiro, André (2020)
The traditional perspective of powerful, centralizing classical urbes should be deconstructed, as it is believed that urbes such as these were variable and dependent on multiple factors, most of them of a social order. The Augustan paradigm, which was heavily used and a defining feature throughout the Empire, later reinforced by Flavian and / or later improvements, or by the localized action of private benefactors, may not have been fully accomplished in a social landscape that, to a great extent, had distinct behavioural codes and that never, truly, acquired classic experiential concepts. More than a city that collapses or faces sudden decline it will never recover from, many of the urban settlements in Lusitania had structural weaknesses, were equipped with expensive devices or that were technically difficult to maintain, which meant that they weighed on the population after the initial investment in their construction. In peripheral areas, these small settlements individually and progressively turned into either a civitas intermortua or oppida labentia